The Headquarters of the Archdiocese of Rosario. (Res Gesta, 2025)
This article aims to contribute to the understanding, from an architectural historical perspective, of the headquarters of the Archdiocese of Rosario, its evolution, and its architectural characteristics. The documented history traces the building's development from the late 19th century, when it was commissioned for private use, to its establishment as a diocesan residence, detailing the successive renovations and functional adaptations of its spaces.
Keywords: History of architecture; Rosario; Archdiocese